The interaction of peptide inhibitors and Aβ protein: Binding mode analysis, inhibition of the formation of Aβ aggregates, and then exert neuroprotective effects - Wu, Yuchen; Guo, Shuang; Wang, Kunli; Kang, Jingjing (Frontiers in Aging Neuroscience, 2023)
Introduction The misfolding and aggregation of β-amyloid (Aβ) easily form Aβ fibers, which are continuously deposited in the brain, leading to the massive generation of amyloid plaques, severely destroying neuronal connections, and promoting Alzheimer’s disease (AD) The occurrence and development of AD is one of the pathogenesis of AD. There is an urgent need to develop inhibitors against Aβ aggregation, which is hopefully a potential way to treat AD. Methods In this study, we first found the crystal structure of the Aβ1–42 receptor protein from the RCSB PDB protein structure database and used the SYBYL X2.0 software for molecular docking, and then used the Peptide Ranker, Innovagen, DPL, and ToxinPred online websites to perform peptides. Predict the activity score, toxicity and water solubility, and then calculate the affinity constant KD value of polypeptide and Aβ through Surface Plasmon Resonance (SPR) experiment. Subsequently, the CCK-8 kit method was used to determine the toxicity of different concentrations of peptides (3.125, 6.25, 12.5, 25, 50, 100, 200 μM) to PC12 cells, and then the peptides and Aβ according to different concentration ratios (1:4, 1:2, 1:1, 1:0.5, 1:0.25, 0:4), this method is also used to detect the effect of peptides on Aβ-induced neurotoxicity. The thioflavin T (ThT) fluorescence method was used to detect the effects of peptides (50 μM) on Aβ (25 μM) aggregation inhibitory effect. Results The results showed that the CScore of YVRHLKYVRHLK peptide molecule docking was 10.0608, the predicted activity score was 0.20, and the KD value was 5.385 × 10−5. The ThT and CCK-8 kit method found that the peptide itself is less toxic to PC12 cells at a concentration of 50 μM, and it has a significant inhibitory effect on the formation of Aβ1–42 aggregates when incubated with Aβ1–42 at a ratio of 1:1 (p < 0.05) and can significantly reduce the PC12 cytotoxicity induced by Aβ1–42 (p < 0.05). Conclusion In conclusion, the polypeptide YVRHLKYVRHLK designed in this study has a neuroprotective effect on PC12 cytotoxicity induced by Aβ1–42. Graphical Abstract